Installed antenna performance in airborne radomes of different profiles - Vukovic, Ana; Sewell, Phillip; Meng, Xuesong; Benson, Trevor M. (Applied Computational Electromagnetics Society, 2016)
In this paper, broadband interactions between an antenna and a radome are modelled using a full wave numerical solver. By accurately describing both the antenna and the radome geometry with a single numerical method, a comprehensive prediction of the performance of the coupled antenna and radome installation is provided. The paper compares how different airborne dielectric radome profiles affect the antenna performance, predicting effects not seen in uncoupled simulations.